2020
DOI: 10.3390/foods9121818
|View full text |Cite
|
Sign up to set email alerts
|

Description of Cumbeba (Tacinga inamoena) Waste Drying at Different Temperatures Using Diffusion Models

Abstract: One approach to improve sustainable agro-industrial fruit production is to add value to the waste generated in pulp extraction. The processing of cumbeba (Tacinga inamoena) fruits generates a significant amount of waste, which is discarded without further application but can be a source of bioactive compounds, among other nutrients. Among the simplest and most inexpensive forms of processing, convective drying appears as the first option for the commercial utilization of fruit derivatives, but it is essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The increase in diffusivity greater than 2.3 times between 50 and 70°C corroborated with results found in other studies which evaluated the drying of vegetable residues such as: passion fruit peels with and without the effect of ultrasound as evaluated by Nascimento et al (2016), where the values for D ef varied from 1.0 × 10 −10 to 2.0 × 10 −10 m 2 /s in samples without ultrasound and temperatures of 50 and 70°C, respectively; orange ( Citrus sinensis ) peel treated with ozone in a study carried out by Bechlin et al (2020), showing increases in D ef varying from 1.15 × 10 −8 to 1.33 × 10 −8 m 2 /s in the samples with the lowest ozone concentrations and temperatures of 50 and 70°C, respectively; banana ( Musa sp .) as evaluated by Tai et al (2021), where the D ef varied from 2.29 × 10 −8 to 3.25 × 10 −8 m 2 /s, at temperatures of 60 and 80°C, respectively; and cumbeba ( Tacinga inamoena ) residues as cited by Ferreira et al (2020), showing values for D ef varying between 2.93 × 10 −9 and 8.14 × 10 −9 m 2 /s, at temperatures of 50 and 70°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in diffusivity greater than 2.3 times between 50 and 70°C corroborated with results found in other studies which evaluated the drying of vegetable residues such as: passion fruit peels with and without the effect of ultrasound as evaluated by Nascimento et al (2016), where the values for D ef varied from 1.0 × 10 −10 to 2.0 × 10 −10 m 2 /s in samples without ultrasound and temperatures of 50 and 70°C, respectively; orange ( Citrus sinensis ) peel treated with ozone in a study carried out by Bechlin et al (2020), showing increases in D ef varying from 1.15 × 10 −8 to 1.33 × 10 −8 m 2 /s in the samples with the lowest ozone concentrations and temperatures of 50 and 70°C, respectively; banana ( Musa sp .) as evaluated by Tai et al (2021), where the D ef varied from 2.29 × 10 −8 to 3.25 × 10 −8 m 2 /s, at temperatures of 60 and 80°C, respectively; and cumbeba ( Tacinga inamoena ) residues as cited by Ferreira et al (2020), showing values for D ef varying between 2.93 × 10 −9 and 8.14 × 10 −9 m 2 /s, at temperatures of 50 and 70°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The values for the energy of activation vary according to the product composition, and the lower the E a the easier it is for the process to occur, that is, less energy will be required for the physical process (Corrêa et al, 2017). Kayran and Doymaz (2017), studying the influence of drying temperature on damson ( Prunus armeniaca L.) residues reported a value for E a to the order of 16.5 kl/mol; Mphahlele et al (2019) reported a value for E a of 21.98 kJ/mol for pomegranate peels; Almeida et al (2020) a mean value for E a of 27.66 kJ/mol for achachairu ( Garcinia humilis ) peels; Tai et al (2021) an E a value of 16.98 kJ/mol for banana peels; Moura et al (2021) an E a value of 18.19 kJ/mol for trapia ( Crateva tapia L.) peels; and Ferreira et al (2020) an E a value to the order of 46.71 kJ/mol for cumbeba ( Tacinga inamoena ) residues.…”
Section: Resultsmentioning
confidence: 99%
“…They also have the advantage of enabling the inclusion of the effect of the shrinkage phenomenon suffered by the product during the drying process (Silva et al, 2012). An analysis of the boundary conditions used for solving the diffusion equation for CD identified two recurrent boundary conditions: equilibrium boundary condition and convective boundary condition (Badaoui et al, 2019; da Silva et al, 2013; do Nascimento et al, 2016; Fernando et al, 2011; Ferreira, Silva, et al, 2020; Henríquez et al, 2014; Kaya et al, 2010; Silva et al, 2012; Wilkins et al, 2018). It is important to mention that if the proper boundary condition to solve the diffusion equation is the first kind or prescribed boundary condition, it is necessary to determine only a single parameter, the effective moisture diffusivity ( D ), to describe the drying kinetics of a product.…”
Section: Introductionmentioning
confidence: 99%
“…An analytical solution to Fick’s second law can be obtained when certain assumptions are made, such as a constant diffusivity and the Dirichlet boundary conditions, for a well-defined geometry such as a cylinder, plate or sphere [ 9 ]. Otherwise, a numerical method is necessary for solving the conservation equation, and inverse optimization may be required to obtain the water diffusivity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%